Adenosine in the lateral hypothalamus/perifornical area does not participate on the CO2 chemoreflex - Rodrigues, Laísa Taís Cabral [UNESP]; Salata, Bruno [UNESP]; Horta-Júnior, José de Anchieta C. [UNESP]; Gargaglioni, Luciane H. [UNESP]; Barros Dias, Mirela [UNESP] (Elsevier, 2020)
The Lateral Hypothalamus/Perifornical Area (LH/PFA) has been shown to be involved with the hypercapnic ventilatory response, in a state-dependent manner. We have demonstrated that purinergic signaling through ATP in the LH/PFA has an excitatory effect in ventilatory response to CO2 in awake rats in the dark phase of the diurnal cycle, but it is unknown whether the ATP metabolite adenosine, acting in the LH/PFA, modulates the ventilatory responses to hypercapnia. Here, we studied the effects of the microdialysis of adenosine (A1/A2 adenosine receptors agonist; 17 mM) and an A1 receptor antagonist (DPCPX; 0.1 mM) into the LH/PFA of conscious rats on ventilation in room air and in 7% CO2 during the light and the dark phases of the diurnal cycle. The microdialysis of adenosine and DPCPX caused no change in the CO2 ventilatory responses of rats during wakefulness or NREM sleep in either the dark or light period. Our data suggest that adenosine in the LH/PFA does not contribute to the hypercapnic ventilatory response in conscious rats.
Keywords: Adenosine; Central chemoreception; DPCPX; Hypercapnia; Hypothalamus